## Final Answer

## Step-by-step Solution

Problem to solve:

Specify the solving method

A binomial squared (difference) is equal to the square of the first term, minus the double product of the first by the second, plus the square of the second term. In other words: $(a-b)^2=a^2-2ab+b^2$

- Square of the first term: $\left(x\right)^2 = x^2$
- Double product of the first by the second: $2\left(x\right)\left(3\right) = 2\cdot 3x$
- Square of the second term: $\left(3\right)^2 = 3^2$

Learn how to solve special products problems step by step online.

$x^2+2\cdot 3x+3^2$

Learn how to solve special products problems step by step online. Expand the expression (x+3)^2. A binomial squared (difference) is equal to the square of the first term, minus the double product of the first by the second, plus the square of the second term. In other words: (a-b)^2=a^2-2ab+b^2<ul><li>Square of the first term: \left(x\right)^2 = x^2</li><li>Double product of the first by the second: 2\left(x\right)\left(3\right) = 2\cdot 3x</li><li>Square of the second term: \left(3\right)^2 = 3^2</li></ul>. Multiply 2 times 3. Calculate the power 3^2.